Indirect determination of the 5'→3' and 3'→5' of the DNA-dependent DNA-polymerase function - Skripal', I.G.; Bezugly, S.V.; Babitschev, V.V. (Биополимеры и клетка, 1994)
Doxorubicin in the concentration of 1 mg/ml and streptonigrin in the concentration 1000 mg/ml each agent separately should by useful to determination of replicative (5'→3') or reparatlve (3'→5') function DNA-polymerase. This enzymes with 5'→3' fully inhibited by doxorubicine but net sensitive to action of streptonigrin in concentration substances mentioned above. And contraverse, DNA-polymerase with 3'→5' function don't sensitive to doxorubicin and it's activity depressed by streptonigrin. Доксорубіцин в концентраци 1 мкг/мл i стрептонігрин в концентраццї 1000 мкг/мл кожний окремо можуть застосовуватися для визначення реплікативної (5'→3') або репаративної (3'→5') функцій ДНК-полімерази. Активність ферменту з реплікативною (5'→3') функцією повністю пригнічується доксорубіцином, але не чутлива до дії стрептонігрину в концентращях, зазначених вище. І, навпаки, активність ДНК-полімерази з репаративною (3'→5') функцією не чутлива до впливу доксорубіцину, але інкубується стрептонігрином. Доксорубицин в концентраци 1 мкг / мл i стрептонигрин в концентрацци 1000 мкг / мл каждый отдельно могут применяться для определения репликативной (5 '? 3') или репаративной (3 '? 5') функций ДНК-полимеразы. Активность фермента с репликативной (5 '? 3') функцией полностью подавляется доксорубицином, но не чувствительна к действию стрептонигрину в концентращях, указанных выше. И, наоборот, активность ДНК-полимеразы с репаративной (3 '? 5') функцией не чувствительна к влиянию доксорубицина, но инкубируется стрептонигрином.